2012
DOI: 10.1186/1471-2458-12-548
|View full text |Cite
|
Sign up to set email alerts
|

An integrated health sector response to violence against women in Malaysia: lessons for supporting scale up

Abstract: BackgroundMalaysia has been at the forefront of the development and scale up of One-Stop Crisis Centres (OSCC) - an integrated health sector model that provides comprehensive care to women and children experiencing physical, emotional and sexual abuse. This study explored the strengths and challenges faced during the scaling up of the OSCC model to two States in Malaysia in order to identify lessons for supporting successful scale-up.MethodsIn-depth interviews were conducted with health care providers, policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(123 citation statements)
references
References 27 publications
2
120
0
1
Order By: Relevance
“…Despite this, there is limited literature describing scaled-up programmes or integrated health system responses (10). …”
mentioning
confidence: 99%
“…Despite this, there is limited literature describing scaled-up programmes or integrated health system responses (10). …”
mentioning
confidence: 99%
“…Despite this debate and recommendations for universal screening, O'Doherty and colleagues could only identify 11 trials of necessary quality for inclusion, with only three trials assessing referrals. This is concerning, as it has been established that women and healthcare providers only endorse screening if disclosure is followed by an adequate response, at a minimum, by referrals to onsite or external services 4 5. Another concern is the quality of screening that is currently taking place; the review found fairly low identification rates of screening compared to prevalence rates estimations in the population.…”
Section: Commentarymentioning
confidence: 99%
“…[13] IPV interventions are complex, and require colla boration between many sectors such as health, social services and criminal justice, as well as systems that facilitate these. They therefore require more than provider training to enable effective programme functioning within a health system.…”
Section: Intimate Partner Violence: How Should Health Systems Respond?mentioning
confidence: 99%
“…Factors relating to health system structure and organisation, as well as external policy constraints, were found to be barriers to implementation. [13] Several system-level factors arising from this case study could be applicable in other contexts. Commitment at policy level was found to be necessary, which could be communicated to service delivery level by incorporating appropriate indicators into routine reporting.…”
Section: Intimate Partner Violence: How Should Health Systems Respond?mentioning
confidence: 99%